22.4k views
5 votes
Subtract (-2x^2+9x-3)-(7x^2-4x+2)

2 Answers

4 votes

Answer:
=-9x^2+13x-5

Explanation:

First, you need to remember the multiplication of signs:


(+)(+)=+\\(-)(-)=+\\(-)(+)=-

Then, to subtract the polynomials given, the first step is to distribute the negative sign:


(-2x^2+9x-3)-(7x^2-4x+2)=-2x^2+9x-3-7x^2+4x-2

And finally, you need to add the like terms.

With this procedure, you get the following result:


=-9x^2+13x-5

User Lior Goldemberg
by
4.7k points
6 votes

For this case we must subtract the following expression:


(-2x ^ 2 + 9x-3) - (7x ^ 2-4x + 2) =

We must bear in mind that:


- * + = -\\- * - = +

We rewrite the expression:


-2x ^ 2 + 9x-3-7x ^ 2 + 4x-2 =

We add similar terms taking into account that equal signs are added and the same sign is placed, while different signs are subtracted and the sign of major is placed:


-2x ^ 2-7x ^ 2 + 9x + 4x-3-2 =\\-9x ^ 2 + 13x-5

Answer:


-9x ^ 2 + 13x-5

User Laplasz
by
4.5k points